DISCUSSION ISSUES OF THE ESSENCE OF FINANCIAL INSTRUMENTS OF PUBLICPRIVATE PARTNERSHIP AND PROBLEMS OF ITS USE IN UKRAINE - SHULIUK, Bohdana (Scientific journal «World of Finance», 2022)
Introduction. Financial participation of state or local authorities in public-private partnership projects is carried out with the help of appropriate tools that allow to create a favorable environment for attracting private sector investment for the implementation of socially important infrastructure projects. However, the financial tools used by the partners in the domestic practice are characterized by low financial attractiveness to investors due to the long period of implementation, limited profitability and high risks in the financial market. Therefore, the use of innovative financial tools for the development of public-private partnership is relevant. The purpose of the article is to generalize scientific approaches to determining the essence of financial instruments of public-private partnership and to identify problems of their effective use in Ukraine. Results. The multifaceted interpretation of the definition of "financial instruments" allowed to form an author’s interpretation of this concept, which means the means of moving financial resources from one entity to another to implement the priorities of financial policy of the state and business structures. The types and components of financial instruments of public-private partnership are singled out, as well as the problems of their use in domestic practice due to the restrictive nature of the action and gaps in the legislation are identified. Conclusions. In domestic practice, it is necessary to improve existing and develop new financial instruments aimed at improving the innovation and investment climate in the field of public-private partnership. At the same time, it is important to strengthen state support for the development of financial instruments of this partnership, which should focus on increasing the capitalization of PPP projects.